2003
DOI: 10.1002/uog.51
|View full text |Cite
|
Sign up to set email alerts
|

The role of fetal nuchal translucency and ductus venosus Doppler at 11–14 weeks of gestation in the detection of major congenital heart defects

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
3
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 21 publications
4
52
3
2
Order By: Relevance
“…6 In a study of 1,040 fetuses at 11th to 14th weeks of gestation, Doppler velocimetry of the ductus venosus in the combination with nuchal translucency improved predictive capacity of CHD detection in chromosomally normal fetuses. 20 In 29 chromosomally normal fetuses, increased nuchal translucency and reversed or absent flow during atrial contraction of the ductus venosus was found, and in 9 fetal echocardiography revealed major CHD. 20 A total of 25 CHD were detected in the whole population, 15 of whom were associated with aneuploidy.…”
Section: To Screen or Not To Screen For Fetal Chd ?mentioning
confidence: 99%
See 4 more Smart Citations
“…6 In a study of 1,040 fetuses at 11th to 14th weeks of gestation, Doppler velocimetry of the ductus venosus in the combination with nuchal translucency improved predictive capacity of CHD detection in chromosomally normal fetuses. 20 In 29 chromosomally normal fetuses, increased nuchal translucency and reversed or absent flow during atrial contraction of the ductus venosus was found, and in 9 fetal echocardiography revealed major CHD. 20 A total of 25 CHD were detected in the whole population, 15 of whom were associated with aneuploidy.…”
Section: To Screen or Not To Screen For Fetal Chd ?mentioning
confidence: 99%
“…20 In 29 chromosomally normal fetuses, increased nuchal translucency and reversed or absent flow during atrial contraction of the ductus venosus was found, and in 9 fetal echocardiography revealed major CHD. 20 A total of 25 CHD were detected in the whole population, 15 of whom were associated with aneuploidy. 20 They concluded that in chromosomally normal fetuses with increased nuchal translucency, assessment of ductus venosus blood flow velocimetry could improve the predictive capacity for an underlying major cardiac defect.…”
Section: To Screen or Not To Screen For Fetal Chd ?mentioning
confidence: 99%
See 3 more Smart Citations